Effects of CSF1R-targeted chimeric antigen receptor-modified NK92MI & T cells on tumor-associated macrophages. (27th August 2018) - Zhang, Ping; Zhao, Songbo; Wu, Chao; Li, Jialu; Li, Zixuan; Wen, Chunmei; Hu, Siyi; An, Gangli; Meng, Huimin; Zhang, Xingding; Yang, Lin
Tumor immunotherapy has shown great progress for the treatment of cancer; however, both endogenous and exogenous T cells are inhibited by the immunosuppressive tumor microenvironment. Tumor-associated macrophages (TAMs) in the microenvironment play pivotal and complex roles in tumor development and progression. Macrophages are categorized as M1 and M2 types. Relevant studies suggest that M2 TAMs correlate with poor prognosis. Colony-stimulating factor 1 receptor (CSF1R) controls the formation, differentiation and function of M2 macrophages, which helps tumors grow, metastasize and secrete immunosuppressive cytokines. The objectives of this study were to establish two types of third-generation chimeric antigen receptors (CARs) that could specifically target human CSF1R, and to introduce the CARs into NK92MI cells and normal human peripheral blood T cells through lentiviral transduction to produce CAR-natural killer (NK) and -T cells. We then tested their cytotoxicity against cell lines and peripheral blood monocytes expressing CSF1R. In vitro experiments confirmed that third-generation CARs had good target specificity and cytotoxicity. It was expected that CAR-NK and -T cells could specifically kill M2 TAMs in the tumor microenvironment and remove their inhibitory effect. Therefore, CSF1R-targeting CAR-NK and -T cells could represent a novel cellular immunotherapy strategy in conjunction with other antibody-based drugs and targeted therapeutics.